Comparison of Robust Circular S and Circular Least Squares Estimators for Circular Regression Model using Simulation - Hadib Abbas, Huda; Najim Abood, Suhail (Journal of Economics and Administrative Sciences, 2022)
In this paper, the Monte-Carlo simulation method was used to compare the robust circular S estimator with the circular Least squares method in the case of no outlier data and in the case of the presence of an outlier in the data through two trends, the first is contaminant with high inflection points that represents contaminant in the circular independent variable, and the second the contaminant in the vertical variable that represents the circular dependent variable using three comparison criteria, the median standard error (Median SE), the median of the mean squares of error (Median MSE), and the median of the mean cosines of the circular residuals (Median A(k)). It was concluded that the method of least squares is better than the methods of the robust circular S method in the case that the data does not contain outlier values because it was recorded the lowest mean criterion, mean squares error (Median MSE), the least median standard error (Median SE) and the largest value of the criterion of the mean cosines of the circular residuals A(K) for all proposed sample sizes (n=20, 50, 100). In the case of the contaminant in the vertical data, it was found that the circular least squares method is not preferred at all contaminant rates and for all sample sizes, and the higher the percentage of contamination in the vertical data, the greater the preference of the validity of estimation methods, where the mean criterion of median squares of error (Median MSE) and criterion of median standard error (Median SE) decrease and the value of the mean criterion of the mean cosines of the circular residuals A(K) increases for all proposed sample sizes. In the case of the contaminant at high lifting points, the circular least squares method is not preferred by a large percentage at all levels of contaminant and for all sample sizes, and the higher the percentage of the contaminant at the lifting points, the greater the preference of the validity estimation methods, so that the mean criterion of mean squares of error (Median MSE) and criterion of median standard error (Median SE) decrease, and the value of the mean criterion increases for the mean cosines of the circular residuals A(K) and for all sample sizes.